2015
DOI: 10.1177/1933719114556483
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PUMA in Follicular Granulosa Cells Regulated by FoxO1 Activation During Oxidative Stress

Abstract: Many studies have demonstrated that oxidative stress-induced apoptosis is a main cause of follicular atresia. Reactive oxygen species (ROS)-induced granulosa cell (GC) apoptosis is regulated by a variety of signaling pathways involving numerous genes and transcription factors. In this study, we found expression of the p53-upregulated modulator of apoptosis (PUMA), a BH3-only Bcl-2 subfamily protein, in ovarian GCs during oxidative stress. By overexpression and knockdown of Forkhead box O1 (FoxO1), we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 45 publications
1
31
0
2
Order By: Relevance
“…In the present study, bGCs were exposed to different levels of in-vitro heat stress and found that heat stress involves compromising the physiological functions of bGCs by increasing intracellular accumulation of ROS, inducing apoptosis and reducing the synthesis of E2 and P4 [7,9,15]. For more understanding, we conducted the transcriptomic study of in-vitro cultured bGCs exposed to heat stress at 39, 40, and 41°C.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present study, bGCs were exposed to different levels of in-vitro heat stress and found that heat stress involves compromising the physiological functions of bGCs by increasing intracellular accumulation of ROS, inducing apoptosis and reducing the synthesis of E2 and P4 [7,9,15]. For more understanding, we conducted the transcriptomic study of in-vitro cultured bGCs exposed to heat stress at 39, 40, and 41°C.…”
Section: Discussionmentioning
confidence: 90%
“…Heat shock 70 kDa protein (HSP70) is a major stress protein induced in mouse GCs by high temperature [9]. Increasing evidence suggests that heat stress induces intracellular ROS concentration [14], resulting in apoptosis of granulosa cells in the mouse [15]. In addition, ROS may subsequently alter the development of bovine embryos during in-vitro oocyte maturation [16].…”
Section: Introductionmentioning
confidence: 99%
“…We also detected the induction of PUMA mRNA and protein in the livers of Chrebp -/-mice fed a 34% fructose diet (Supplemental Figure 6, E and F). Meanwhile, FOXO1 and p53 protein levels were comparable between WT and Chrebp -/-livers ( Figure 1J), indicating that the induction of PUMA was probably not due to FOXO1 and p53, two known transcription activators of Puma (26,27).…”
Section: A Hfrd Activates the C/ebp Homologous Protein-mediated Apoptmentioning
confidence: 83%
“…FoxO1 regulates Bim gene expression by binding to its promoter in oxidative stress-induced apoptosis [23]. Moreover, FoxO1 induces cell apoptosis via modulating Puma expression in oxidative stress-induced MGCs [24]. …”
Section: Introductionmentioning
confidence: 99%